Case Report 18F-FDG PET/CT of Pseudomyogenic Hemangioendothelioma. (May 2020) - Plouznikoff, Nicolas; Mourad, Stephanie A.; Turpin, Sophie; Turcotte, Robert E.; Mitchell, David A.; Lambert, Raymond
Abstract : Abstract: Hemangioendotheliomas are a heterogeneous group of vascular neoplasm that may affect the liver, bone, and soft tissues. Among its variants, pseudomyogenic hemangioendothelioma is rarely encountered. Pseudomyogenic hemangioendothelioma is usually characterized by multiple soft tissue lesions, with occasional bone lesions. Fewer than 20 cases with exclusive involvement of bone structures have been reported. We describe a case of pseudomyogenic hemangioendothelioma involving multiple bony structures but without soft tissue involvement in a 7-year-old girl, imaged with 18 F-FDG PET/CT at diagnosis and during treatment with mammalian target of rapamycin inhibitors.